Size dependent properties of Gd3+-free versus Gd3+-doped carbon dots for bioimaging application - Nazym Zhylkybayeva; Konstantin Paliienko; Anna Topchylo; Alexander Zaderko; Alain Géloën; Tatiana Borisova; Liudmyla Grishchenko; Ruslan Mariychuk; Valeriy Skryshevsky; Gauhar Mussabek; Vladimir Lysenko (Scientific Reports)
Abstract Gd3+- free carbon dots (CDs) were synthesized by one-step solvothermal method using urea, citric acid and 3-(trifluoromethyl)aniline as precursors. Additionally, Gd3+-doped CDs were prepared by incorporating gadolinium chloride (Gd3+ ions) into the synthesis. Size selection of the purified CDs was achieved through filter membranes ranging from 3 kDa to 100 kDa. The chemical composition and optical properties of the obtained samples were characterized by Energy dispersive X-ray (EDX), Fourier-transform infrared spectroscopy (FTIR), Dynamic Light Scattering (DLS), proton relaxation time measurements, Ultraviolet–visible (UV-vis) and fluorescence spectroscopies. A comparative analysis revealed a strong size-dependent behavior in the optical properties of both Gd3+-doped and Gd3+-free CDs. Furthermore, in vitro tests confirmed the non-cytotoxicity of Gd3+-doped CDs, indicating their potential applicability in biomedicine for magnetic resonance imaging (MRI) and red fluorescence-based cell and tissue imaging.